Peritoneal Dialysis Catheter Emplacement by Advanced Laparoscopy: 8-year Experience from a Medical Center of China - Min Mo (Nature Portfolio, 2017)
Abstract Laparoscopic experience and relevant reports about PD catheter emplacement in Chinese patients are seldom. In this study, we described our experience with advanced laparoscopy for PD catheter implantation in Chinese patients. There were one hundred and thirty Chinese patients accepted advanced laparoscopic approach for PD catheter emplacement in this study. Six of 26 patients with prior abdominal operations had abdominal adhesion, while six of 104 patients without prior abdominal surgeries showed abdominal adhesion. Operation time required 10 to 180 minutes. During a mean follow-up time of 26.46 months, the catheter complications were shown as outflow obstruction (n = 6, 4.62%), pericatheter leaking (n = 3, 2.31%), hydrocele of tunica vaginalis (n = 1, 0.77% in all), and umbilical hernia (n = 2, 1.54%). Cumulative revision-free survival probability for catheter loss from mechanical complications at 8 years was 0.95. During the postoperative follow-up ranged between 6 and 106 months, 98 patients (75.38%) were still on CAPD, 17 patients (13.08%) died, 8 patients (6.15%) were transferred to hemodialysis, 6 patients (4.62%) received kidney transplantation, and 1 patient (0.77%) showed improved renal function. These results showed that PD catheter placement with advanced laparoscopy is a safe and effective approach in Chinese patients with or without prior abdominal surgeries.